1972
DOI: 10.3181/00379727-139-36250
|View full text |Cite
|
Sign up to set email alerts
|

The Integrity of Mammary Alveolar Cells in Two Consecutive Lactations

Abstract: Reece and Warbritton ( l ) , using the colchicine technique, reported that mammary glands of rats pregnant during the first lactation exhibited very little mitotic activity between the fifth day of lactation and the second parturition. This indirect evidence indicated that some of the secretory cells present in the first lactation were probably present in the second lactation in rats pregnant during the first lactation. Hence, it was desirable to obtain direct evidence on this problem.The use of tritiated thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…As mentioned previously, the importance of the extracellular matrix on mammogenesis also has been suggested in cattle (Capuco et al, 1997). Pitkow et al (1972) also demonstrated reduced milk yield in CM rats, but provided evidence that omitting the dry period resulted in an increase in mammary cell carryover from one lactation to the next. In humans, women who nursed through the last trimester of pregnancy had infants with a 15% reduction in weight gain during the first month postpartum (Marquis et al, 2002).…”
Section: Shortened or Omitted Dry Period Hypotheses Regarding Dry Period Requirementsmentioning
confidence: 68%
“…As mentioned previously, the importance of the extracellular matrix on mammogenesis also has been suggested in cattle (Capuco et al, 1997). Pitkow et al (1972) also demonstrated reduced milk yield in CM rats, but provided evidence that omitting the dry period resulted in an increase in mammary cell carryover from one lactation to the next. In humans, women who nursed through the last trimester of pregnancy had infants with a 15% reduction in weight gain during the first month postpartum (Marquis et al, 2002).…”
Section: Shortened or Omitted Dry Period Hypotheses Regarding Dry Period Requirementsmentioning
confidence: 68%
“…There is evidence in rats for increased carry-over of mammary secretory cells from one lactation to the next when the dry period is omitted (Pitkow et al 1972). We have no direct evidence for or against this in goats.…”
Section: Mammary Gland Analysismentioning
confidence: 71%
“…As a result, a higher number of old alveolar cells are being carried over from the previous lactation to the next in the continuously milked mammary gland. This has also been observed in rats with no dry period in between 2 lactations (Pitkow et al, 1972). The cows in the study by Capuco and Akers (1999) were killed before parturition, and the effect on their milk production in the next lactation therefore not known.…”
Section: Introductionmentioning
confidence: 83%